An Integrative Methodology for Organizational Oppositions: Aligning Grounded Theory and Discourse Analysis. (October 2019) - Fairhurst, Gail T.; Putnam, Linda L.
The study of organizational tensions, contradictions, dialectics, and paradoxes is on the rise in the organizational sciences. This article sets forth an integrative methodology for studying these oppositional phenomena by aligning grounded theory techniques with the little "d" and big "D" orientations of organizational discourse analysis. This integrative methodology not only aids in identifying and determining various types of organizational oppositions and responses to them, but also fosters assessment of their potential power effects and micro organizing dynamics. We provide detailed steps for undertaking this integrative methodology, illustrate these steps with an extended example, and conclude with a discussion of new directions for using this approach.